(untitled) (Filološke studije, 2020)
Danila Vassilieff (1897 –1958) was a Russian émigré artist who lived and worked in Australia. By far the largest and most significant part of his painterly and sculptural oeuvre Vassilieff executed on Australian soil, in the states of New South Wales and Victoria. This article explores Vassilieff’s visual arts ideas and idiom created within the parameters of his Russian and Slav cultural memory and characterised by his émigré experience. It argues that Vassilieff’s art was fully formed only after the artist’s experiencing an existence of a permanent émigré in Australia and that both his ideas and his idiom flourished in opposition to the cultural traditions of his new environment. Vassilieff’s relationship with his Russian and Slav cultural heritage was traced in the monograph Imaginary homelands, the art of Danila Vassilieff (Bojic 2007). This essay complements the extant research by examining Vassilieff’s relationship with his Australian environment as reflected in his work. Vassilieff’s experience of a permanent émigré formed his visual arts idiom and provided for the large pool of themes and topics in his work. Much of his oeuvre bridged the varied cultural traditions of his Russian homeland and the hardship he experienced living in a barren Australian land. There were two reasons for this. One was the artist’s position of being an émigré; the other was that of being an artist. His initial alone-ness in a new Australian environment allowed for his one-ness and thus contributed to the uniqueness of his expression and his oeuvre, recognised as such later on by his Australian peers. The chronic trauma of being a permanent émigré was a continual feature of Vassilieff’s life and of his work. His deep feelings of nostalgia were an essential quality of his existence in exile. The artist himself would attempt to counterbalance this with his all-pervasive energetic good will and his refined sense of humour and sweet irony on occasions leading into a sarcasm, evident in many of his works.